Exciton-polariton effects in a pencil-like ZnO microwire. (December 2015) - Wang, Yinglei; Zhang, Zhe; Dong, Hongxing; Xie, Wei; Hu, Tao; Chen, Zhanghai
Abstract: We demonstrate the observation of the strong excitons-photons coupling in pencil-like ZnO microwires at room temperature. The pencil-like ZnO microwires with high optical quality were fabricated by using a carbothermal growth method at 1100 °C. The strong coupling of excitons and photons is evidenced by using angle-resolved photoluminescence spectroscopy. By scanning excitations spot from the arm to the tip of the pencil-like ZnO microwires, we found that the confinement of the tip is weaker than that of the arm due to the shrinked size. With increasing the excitation power, the lowest energy states of exciton-polariton modes are remarkably populated, and lasing phenomena are observed. By using the coupled oscillator model, the polariton effect can be well described. Highlights: We fabricate the pencil-like ZnO microwires with high optical quality. We demonstrate the robust exciton-polariton effects in the pencil-like ZnO microwires. We realize the polariton lasing in the pencil-like ZnO microwires.